Our plastic age - Thompson, Richard C. (The Royal Society Publishing, 2009)
Within the last few decades, plastics have revolutionized our daily lives. Globally we use in excess of 260 million tonnes of plastic per annum, accounting for approximately 8 per cent of world oil production. In this Theme Issue of Philosophical Transactions of the Royal Society, we describe current and future trends in usage, together with the many benefits that plastics bring to society. At the same time, we examine the environmental consequences resulting from the accumulation of waste plastic, the effects of plastic debris on wildlife and concerns for human health that arise from the production, usage and disposal of plastics. Finally, we consider some possible solutions to these problems together with the research and policy priorities necessary for their implementation.